2021
DOI: 10.1017/s0007485321000948
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of secondary metabolites in bean cultivars and their impact on the nutritional performance ofSpodoptera littoralis(Lep.: Noctuidae)

Abstract: Spodoptera littoralis (Boisd) is globally recognized as a destructive polyphagous insect pest of various crops in the world. It is commonly managed by chemical pesticides, which can cause deleterious effects such as environmental pollution, toxicity to non-target organisms and the emergence of secondary pests. Hence, investigations into alternative pest control strategies such as the use of resistant host plant cultivar against S. littoralis is important. This study aimed to explore the nutritional performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 70 publications
1
30
0
Order By: Relevance
“…In addition, the intrinsic rate of increase ( r ) of S. littoralis was positively correlated with starch content, which is congruent with the relatively high r value characterizing S. littoralis that developed on Arabi. Furthermore, these results are consistent with the previous investigations that related macronutrient and biochemical traits of various plants to herbivore performance [ 4 , 18 , 39 , 40 ]. The r value is related to life history traits, such as developmental time, survival rate, and fecundity.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In addition, the intrinsic rate of increase ( r ) of S. littoralis was positively correlated with starch content, which is congruent with the relatively high r value characterizing S. littoralis that developed on Arabi. Furthermore, these results are consistent with the previous investigations that related macronutrient and biochemical traits of various plants to herbivore performance [ 4 , 18 , 39 , 40 ]. The r value is related to life history traits, such as developmental time, survival rate, and fecundity.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the economic importance of S. littoralis on legumes, there have been no life table or performance investigations published for this pest on this important crop. Previous studies with various other plant species have revealed significant variation in host plant suitability to S. littoralis [ 4 , 26 , 27 , 28 ]. In general, the use of plant tolerance or resistance traits as a means of managing S. littoralis has been relatively neglected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations